Improving the Quality of Teaching in Using the “E-Mole B” Learning Application in the MGMP PJOK Teacher Community of Kuningan Regency (ABDIMAS: Jurnal Pengabdian Masyarakat, 2025)
The ability of teachers to provide teaching materials is very important. The application of technology is believed to help teachers and students better understand the given movement tasks. Based on the problems faced, the Community Service Team at Muhammadiyah University of Kuningan carried out activities to address the issues encountered by its partners. Community service activities aim to improve the ability of teachers to provide teaching materials by implementing E-Mole B technology. E-Mole B is an Android-based application. In the application, there are systematic Badminton learning movement tasks. The movement tasks are in the application that makes it easy for students to learn them through their respective gadgets. This activity was carried out on all members of the MGMP PJOK SMP Kuningan Regency, totaling 15 participants. The method used was the Coaching Clinic, which consisted of 4 sessions. The material provided consisted of socialization, training, peer technology and mentoring, and evaluation. The results of activities in the community showed an increase in the ability of teachers in implementing the use of E-Mole B technology in learning the game of Badminton.